Nilotanypus Kieffer from China (Diptera: Chironomidae: Tanypodinae) - Cheng, Ming; Wang, Xinhua (Zootaxa, 2006)
The genus Nilotanypus is recorded from the Oriental region for the first time. Two new species, N. polycanthus and N. quadratus, from Oriental China are described and figured as males. N. dubius (Meigen) is recorded from northern China. A key to the males of all known Nilotanypus is presented.